Immunization in Pregnant and Breastfeeding Women (Turkey Health Literacy Journal, 2020)
Immunization in our country as part of the Extended Immunization Program (GBP) since 1981 services are offered. The purpose of the program can be prevented by vaccinating babies, children and adults immunization by vaccinating before the period when the risk of getting diseases is highest and to prevent injury and death from these diseases.In this review, before pregnancy according to the adult vaccination schedule, pregnant women whose vaccines are missing; current vaccines applications It is aimed to provide sensitivity on the subject by examining in the light of current information.